The role of social support and emotional intelligence in fostering resilience among Malaysian undergraduate students - Abdul Patah, Salwa; Mat Noor, Noor Athirah Syazana; Harun, Mohd Ferdaus; Mohd Yusof, Halimah (Asian Scholars Network (ASNet), 2024)
One of the challenges impeding Malaysia's economic growth in 2024 is the condition of the global economy, which would raise the country's unemployment rate. There are generally 224,000 new graduates born in Malaysia every year, yet only 127,000 highly skilled jobs are available. This means that Malaysia produces an excessive number of university graduates. The shortage of job prospects will make it harder for the next graduates to find jobs. Hence, graduates from universities need to be psychologically ready to handle uncertain circumstances. Employers do believe that university graduates must acquire workplace resilience before beginning their careers. People perceive a resilient individual as tough, deserving of respect, and successful. Empirical evidence supports the claim that university students' emotional intelligence and social support play a major role in determining their resilience. Thus, the purpose of this study is to find out the extent to which students’ resilience correlated with social support and emotional intelligence at six Malaysian public universities. To collect data, we conducted a cross-sectional survey with 387 students. The results show a considerable positive correlation between resilience, emotional intelligence, and social support. This study demonstrates the potential influences of social support and emotional intelligence on the development of resilience in Malaysian undergraduate students. The unpredictable nature of the global economy signifies that changes in the university environments are inevitable. This study suggests that enhancing the university's general courses and co-curriculum module will foster students’ willingness to take risks and increase their self-confidence, both of which will increase resilience.